Soft neurological signs and prenatal alcohol exposure: a population‐based study in remote Australia. (15th March 2016) - Lucas, Barbara R; Latimer, Jane; Fitzpatrick, James P; Doney, Robyn; Watkins, Rochelle E; Tsang, Tracey W; Jirikowic, Tracy; Carmichael Olson, Heather; Oscar, June; Carter, Maureen; Elliott, Elizabeth J
Abstract : Aim: To identify soft neurological signs (SNS) in a population‐based study of children living in remote Aboriginal communities in the Fitzroy Valley, Western Australia, born between 2002 and 2003 and explore the relationship between SNS, prenatal alcohol exposure (PAE), and fetal alcohol spectrum disorders (FASD). Method: The presence of SNS was assessed using the Quick Neurological Screening Test, 2nd edition (QNST‐2), which has a total maximum score of 140. Higher scores indicated more SNS. 'Severe discrepancy' was defined as scores less than or equal to the fifth centile while 'moderate discrepancy' represented scores from the sixth to the 24th centile. Children were assigned FASD diagnoses using modified Canadian FASD diagnostic guidelines. Results: A total of 108 of 134 (80.6%) eligible children (mean age 8y 9mo, SD=6mo, 53% male) were assessed. The median QNST‐2 Total Score for all participants was within the normal category (19.0, range 4–66). However, the median QNST‐2 Total Score was higher in children with than without (1) PAE ( r =0.2, p =0.045) and (2) FASD ( r =0.3, p =0.004). Half (8/16) of children scoring 'moderate discrepancy' and all (2/2) children scoring 'severe discrepancy' had at least three domains of central nervous system impairment. Interpretation: SNS were more common in children with PAE or FASD, consistent with the known neurotoxic effect of PAE. The QNST‐2 is a useful screen for subtle neurological dysfunction indicating the need for more comprehensive assessment in children with PAE or FASD. What this paper adds: The median Quick Neurological Screening Test, 2nd Edition (QNST‐2) Total Scores of the cohort approximated population norms. Despite this, poor performance was evident in some tasks. Children with prenatal alcohol exposure/fetal alcohol spectrum disorders (PAE/FASD) had significantly higher median QNST‐2 Total Scores than children without. The QNST‐2 is a useful screening instrument for brain dysfunction. It indicates in children with PAE/suspected FASD when more comprehensive assessment is needed. This article is commented on by Bertrand on pages794–795 of this issue.